Booster doses of COVID-19 vaccines for patients with haematological and solid cancer: a systematic review and individual patient data meta-analysis. (September 2022) - Mai, Aaron Shengting; Lee, Ainsley Ryan Yan Bin; Tay, Ryan Yong Kiat; Shapiro, Lauren; Thakkar, Astha; Halmos, Balazs; Grinshpun, Albert; Herishanu, Yair; Benjamini, Ohad; Tadmor, Tamar; Shroff, Rachna T.; LaFleur, Bonnie J.; et al.
Abstract: Importance: Patients with cancer have an increased risk of severe disease and mortality from COVID-19, as the disease and antineoplastic therapy cause reduced vaccine immunogenicity. Booster doses have been proposed to enhance protection, and efficacy data are emerging from several studies. Objective: To evaluate the proportion of COVID-19 primary vaccination non-responders with cancer who seroconvert after a booster dose. Methods: PubMed, EMBASE, CENTRAL and medRxiv were searched from 1st January 2021 to 10th March 2022. Quality was assessed using the Joanna Briggs Institute Critical Appraisal checklist. Results: After the eligibility assessment, 22 studies were included in this systematic review and 17 for meta-analysis of seroconversion in non-responders, pooling a total of 849 patients with haematological cancer and 82 patients with solid cancer. Haematological cancer non-responders exhibited lower seroconversion at 44% (95% CI 36–53%) than solid cancer at 80% (95% CI 69–87%). Individual patient data meta-analysis found the odds of having a meaningful rise in antibody titres to be significantly associated with increased duration between the second and third dose (OR 1.02, 95% CI 1.00–1.03, P ≤ 0.05), age of patient (OR 0.960, 95% CI 0.934–0.987, P ≤ 0.05) and cancer type. With patients with haematological cancer as a reference, patients with lung cancer had 16.8 times the odds of achieving a meaningful increase in antibody titres (OR 16.8, 95% CI 2.95–318, P ≤ 0.05) and gastrointestinal cancer patients had 25.4 times the odds of achieving a meaningful increase in antibody titres (OR 25.4, 95% CI 5.26–492.21, P ≤ 0.05). Conclusions: administration of a COVID-19 vaccine booster dose is effective in improving seroconversion and antibody levels. Patients with haematological cancer consistently demonstrate poorer response to booster vaccines than patients with solid cancer. Highlights: 80% of patients with previously non-seroconverted solid cancer do so after a third dose. Less than half of patients with haematological cancer seroconvert after a third dose. After the third dose, antibody titres rose up to 30-fold across studies. Individual patient data (IPD) revealed that gastrointestinal (GI) and lung cancers performed best among patients with solid cancer. More days between second and third doses increased the odds of a 2x rise in titres.